Tourism in a New Role: The Relation between Destination Development and Social Well-Being - Tivadar Mahr (Proceedings of the ENTRENOVA - ENTerprise REsearch InNOVAtion Conference, Rovinj, Croatia, 8-9 September 2016, 2016)
Tourism, making up an ever growing share of Hungarian GDP has become a key factor in the branches of national economy. Tourism Destination Management organisations (TDMs) guide and coordinate the life of tourism as bodies operating on local and regional levels. These organisations were so far investigated from the vocational aspect of tourism, or their competitiveness was analysed from the management side. The research into these organisations from the point of view of innovation is a new element: how large and what kind of performance was delivered by these groups in the wake of the subsidies of the past EU budgetary cycle. Innovation research analyses – according to the Quadruple helix model – the fourth helix, as a media-based civic community, highlighting the importance of civic society and its role in the efficiency of innovation systems. TDM organisations shall be considered as media-based civic groups shaping communities and the extent and dimension of their role in implementing social innovation be analysed. The research conducted in 2016 investigates this correlation system hypothesising that TDM organisations are key workshops of social innovation and thus one of the pillars of social well-being. The aim of this paper is to prove, or deny: TDM organisations are the birthplaces of – social – innovation and the cooperation system of TDM organisations supports the development of social well-being.
Keywords: O3; O35; 330; Tourism Destination Management; innovation systems; social innovation; society